2022
DOI: 10.1042/bsr20211406
|View full text |Cite
|
Sign up to set email alerts
|

Specific interactions of peripheral membrane proteins with lipids: what can molecular simulations show us?

Abstract: Peripheral membrane proteins can reversibly and specifically bind to biological membranes to carry out functions such as cell signalling, enzymatic activity, or membrane remodelling. Structures of these proteins and of their lipid-binding domains are typically solved in a soluble form, sometimes with a lipid or lipid headgroup at the binding site. To provide a detailed molecular view of peripheral membrane protein interactions with the membrane, computational methods such as molecular dynamics (MD) simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 210 publications
(294 reference statements)
2
25
0
Order By: Relevance
“…Indeed, these data are in agreement with the previous CG study of Dias et al, which showed spontaneous binding of Aβ 1-42 fibrils with membrane [21]. Our simulations reveal that both charged and hydrophobic residues participate in the binding with the membrane, in agreement also with previous studies reporting that both basic and hydrophobic amino acid residues play an important role in peripheral protein binding with the membranes [39,40]. Furthermore, we noticed that C-terminal residues significantly participate in membrane binding, which is also in line with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, these data are in agreement with the previous CG study of Dias et al, which showed spontaneous binding of Aβ 1-42 fibrils with membrane [21]. Our simulations reveal that both charged and hydrophobic residues participate in the binding with the membrane, in agreement also with previous studies reporting that both basic and hydrophobic amino acid residues play an important role in peripheral protein binding with the membranes [39,40]. Furthermore, we noticed that C-terminal residues significantly participate in membrane binding, which is also in line with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, these data are in agreement with the previous CG study of Dias et al, which showed spontaneous binding of Aβ 1–42 fibrils with membrane [21] . Our simulations reveal that both charged and hydrophobic residues participate in the binding with the membrane, in agreement also with previous studies reporting that both basic and hydrophobic amino acid residues play an important role in peripheral protein binding with the membranes [42] , [43] . Furthermore, we noticed that C-terminal residues significantly participate in membrane binding, which is also in line with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…In this section, the main objective is to better understand the interactions between the heterotrimer UbiJ-UbiK 2 and the lipid bilayer membrane. A multi-scale MD simulation approach, i.e., a series of CG and all-atom MD simulations [ 35 ], was used to tackle this question. For both types of MD simulations, the lipid bilayer membrane was described as realistically as possible with a composition of POPE:70, POPG:25, LNDCL2:5.…”
Section: Resultsmentioning
confidence: 99%